2019
DOI: 10.2516/ogst/2019028
|View full text |Cite
|
Sign up to set email alerts
|

Determination and evaluation of minimum miscibility pressure using various methods: experimental, visual observation, and simulation

Abstract: This research proposes a simultaneous technique using various methods to yield the most reliable Minimum Miscibility Pressure (MMP) value. Several methods have been utilized in this study including slim tube test, swelling test, vanishing interfacial tension test, visual observation during swelling test and vanishing interfacial tension test, and simulation. The proposed method may reduce the uncertainty and avoid doubtful MMP. The method can also demonstrate discrepancies among the results. There were two sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Thus, it is advantageous to use this technique. It also proves that the slim-tube test is an appropriate method to estimate MMP, as suggested by Abdurrahman et al 17,25,26 Second, the MMP is determined through simulation using the equation of state (EOS). Third, visual observation is conducted using photos or videos, as previously done by Jessen and Orr 22 and Abdurrahman et al 17,25,26 In the current case, the shape of the oil drop is observed until it disappears in the display cell.…”
Section: Introductionmentioning
confidence: 79%
“…Thus, it is advantageous to use this technique. It also proves that the slim-tube test is an appropriate method to estimate MMP, as suggested by Abdurrahman et al 17,25,26 Second, the MMP is determined through simulation using the equation of state (EOS). Third, visual observation is conducted using photos or videos, as previously done by Jessen and Orr 22 and Abdurrahman et al 17,25,26 In the current case, the shape of the oil drop is observed until it disappears in the display cell.…”
Section: Introductionmentioning
confidence: 79%
“…Compared with other methods, this method is more in line with the characteristics of oil and gas displacement process in the porous medium of crude oil reservoir. Moreover, the influence of unfavorable factors such as heterogeneity, mobility ratio, viscous fingering and gravity separation of lithology can be eliminated to the greatest extent [57][58][59]. Therefore, the long-slim-tube displacement experiment method was used to determine the MMP in the research area.…”
Section: The Experimental Process Of Determining the Mmpmentioning
confidence: 99%
“…There are several methods to determine MMP. 23 These methods include experimental methods and empirical correlations such as slim tube test, swelling/extraction test, vapor−liquid equilibrium, rising bubble apparatus (RBA), slim tube composition simulator, and vanishing interfacial tension (VIT) test. Some laboratory data�machine learning meth-ods�have been used in various areas of EOR, especially in gas injection methods, to find out MMP.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include experimental methods and empirical correlations such as slim tube test, swelling/extraction test, vapor–liquid equilibrium, rising bubble apparatus (RBA), slim tube composition simulator, and vanishing interfacial tension (VIT) test. Some laboratory datamachine learning methodshave been used in various areas of EOR, especially in gas injection methods, to find out MMP. ,−, Several experimental methods have been introduced by researchers for MMP prediction. , However, some researchers believe that each method has distinctive disadvantages in predicting accurate values. , Nevertheless, some investigators tried to introduce modified methods to reduce the uncertainties. ,, Here are some of the most important and common methods to describe: an experimental method that is accepted by the petroleum community as a standard measurement is slim tube test . In this method, gas flows through the long coil packed with porous material and saturated with live oil and then MMP is determined by the measurement of oil recovery factor, injected pore volumes, and pressure. , The drawback of this method is that it is relatively time-consuming and high in cost. , Another MMP measurement approach that has been used for about 3 decades is the RBA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation